PEMBIAYAAN BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN PADA REHABILITASI MEDIS - Hanna Wijaya; Handar Subhandi Bakhtiar (Jurnal Medika Hutama, 2022)
Jamsostek is implemented by the Health Social Security Organizing Agency which encompasses BPJS Employment Services and BPJS Health Services. Cardiac rehabilitation is done out so that the post-morbid cardiovascular system increases and is optimal. BPJS sets new laws on cataracts, delivery, and medical rehabilitation. Medical Rehabilitation control visits may only be held twice a week. Meanwhile, for conditions that do require medical rehabilitation more than 2 times a week, it is considered quite a lot, one of which is cardiac surgery medical rehabilitation. As a result, patients will use their own resources to pay for treatment because BPJS only bears rehabilitation costs twice a week. This study adopts a research technique that reviews the juridical normative. Medical rehabilitation is a new field of specialization in medical science. This field of science examines the care of patients with impairments as a whole, neuromuscular structure, loss of function arising from the heart and lungs structure, bone muscle structure, as well as physical and social mental illnesses that accompany the disability. BPJS Health is a public legal entity that is responsible for patients and is beneficial for establishing health insurance plans for all Indonesian people. Foreign citizens are also allowed if they work within a period of six months in Indonesia. BPJS Kesehatan covers medical rehabilitation services based on medical symptoms and service standards, as well as current laws and regulations. Currently, rehabilitation can only be carried out 2 times in two weeks or a maximum of only eight times per month and is in contrast to the old one, which can rehabilitate up to 29 times per month. This renders health services no longer covered by BPJS Kesehatan. This constraint can undoubtedly make it tough for medical rehabilitation patients. If the intensity of service is reduced, this can slow down the recovery process of cardiac surgery patients.